Leishmaniasis: Recent epidemiological studies in the Middle East - Knight, Chinyere A.; Harris, David R.; Alshammari, Shifaa O.; Gugssa, Ayele; Young, Todd; Lee, Clarence M. (Frontiers in Microbiology, 2023)
Leishmaniasis, one of the most neglected tropical diseases (NTDs), is the third most important vector-borne disease worldwide. This disease has a global impact and severity of the infection and is greatest in the Middle East. The agent of infection is a protozoan parasite of the genus, Leishmania, and is generally transmitted by blood-sucking female sandflies. In humans, there are three clinical forms of infection: (1) cutaneous (CL), (2) mucocutaneous (ML), and (3) visceral leishmaniasis (VL). This review aims to discuss the current epidemiological status of leishmaniasis in Saudi Arabia, Iraq, Syria, and Yemen with a consideration of treatment options. The elevated risk of leishmaniasis is influenced by the transmission of the disease across endemic countries into neighboring non-infected regions.